Design and Prototyping of Shredded Plastic Waste Dryer Samuel - Rahardian, Samuel
Plastic waste was increasing in number. An effort was needed to reduce the amount of plastic waste. With plastic waste recycling technology, the increment rate of the plastic waste could be reduced. In this recycling process there was several problems occured limiting the production rate. One of the problems was the time to dry the shredded plastic waste. The drying process was using the sun that could be affected by the weather and takes a longer time. One of the solution for reducing the time needed was to make a device that could dries the plastic in short amount of time. This final project purpose is to build a drying device prototype for shredded plastic waste. The prototype of the dryers was drying the shredded plastic waste with short amount of time, but several problems occured that made non-uniform drying process. To solve that problem, a paddle was needed to ensure the drying process spreading evenly among the shredded plastic. It was observed that additional paddle increased the rate of drying.